Self Leadership Training in Emotion Management for Persit Kartika Candra Kirana (KCK) Branch 3 Dispsiad Members, Bandung, West Java - Diawati, Prety; Sugesti, Hesty (Indonesian Journal of Community Services Cel, 2022)
Persit KCK Branch 3 Dispsiad Branch III PG MABESAD, is a Persit organization (Army Wives Association) which is under the Army Psychology Service located at Jalan Sangkuriang No. 53 in the city of Bandung, West Java. Her mission is to create harmony among all the soldiers' wives in the Dispsiad environment. In an organization, the diversity and differences that each individual brings will create the characteristics and personality of each individual to make it colorful in the interactions between fellow persit members so that each persit member is expected to be able to control herself. Problems that may occur can be caused by miscommunication between individuals which is a factor in the emergence of differences of opinion, disputes, and even disputes which is contrary to the purpose of establishing Persit KCK which is based on kinship. Based on this, there is a need for training for first mothers in cultivating a soul to lead themselves, especially in managing emotions so that they can minimize or even eliminate unexpected things. Emotional management training for Persit KCK Branch 3 Dispsiad has an impact on increasing Persit's ability to control himself, show trustworthiness, behave with sincerity,  have an adaptable attitude, and have a high ability to innovate so that he can be accepted in a social environment.